2020
DOI: 10.1519/jsc.0000000000003741
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Post-match Recovery Response in Male Rugby: A Systematic Review

Abstract: To minimize underperformance, injury and illness, and to enhance readiness for training and matchplay, post-match responses are commonly monitored within professional rugby. As no clear consensus exists regarding the magnitude and duration of post-match recovery, this review summarized literature (17 studies yielded from literature searching/screening) reporting neuromuscular (countermovement jump; CMJ: peak power output; PP, flight-time; FT), biochemical (creatine kinase; CK), endocrine (cortisol; C, testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Whereas in the current study the frequency and duration reported can be interpreted confidently, as the reports were precisely captured via microtechnology units. The lower training volume compared to those reported by McCormack et al [ 26 ] may not come as a surprise, as U19 players are employed as professional athletes, but are part-time, often training while studying or working [ 23 , 26 , 27 ]. Yet they are still expected to follow high frequency training programmes ensuring they are adequately prepared for senior professional rugby league [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in the current study the frequency and duration reported can be interpreted confidently, as the reports were precisely captured via microtechnology units. The lower training volume compared to those reported by McCormack et al [ 26 ] may not come as a surprise, as U19 players are employed as professional athletes, but are part-time, often training while studying or working [ 23 , 26 , 27 ]. Yet they are still expected to follow high frequency training programmes ensuring they are adequately prepared for senior professional rugby league [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As both excessive and insufficient training load may impede athletic development, understanding the specific training loads undertaken by academy rugby league players is important for the planning of future training to maximise athletic performance, injury prevention, playing progression, and general wellbeing [ 3 ]. Differences in training load, alongside differences in certain physical capabilities associated with specific playing positions and standards, may influence one’s understanding of appropriate training prescription [ 1 , 27 ]. No study has quantified an academy rugby league pre-season period, considering positional demands for both field- and resistance-based training loads.…”
Section: Introductionmentioning
confidence: 99%
“…Further, rugby sevens is more homogenous for positional groups, compared to the other rugby codes (Ross et al, 2015). Whilst previous work has summarised and examined the post-match fatigue and recovery across the rugby codes, this research did not explore the influence of collision characteristics on recovery measures (Aben et al, 2020). This omission is important, given the purported contribution of collisions to elevated psycho-physiological and biomechanical load outlined above.…”
Section: Introductionmentioning
confidence: 96%
“…However, in the context of exposure to an exercise bout (such as rugby match-play), and in the context of this review, fatigue can be considered the disruption of homoeostasis that negatively impacts the ability to produce and apply force (Vøllestad, 1997). Fatigue processes possess acute and chronic dimensions and are therefore time-dependent, although they typically recover toward baseline following the acute effects of match-play (Aben et al, 2020). Muscle damage as a result of match-related activities has the potential to exacerbate fatigue symptoms and delay recovery (Peake et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation